A free-standing, hybrid TiO2/K-OMS-2 hierarchical nanofibrous membrane with high photocatalytic activity for concurrent membrane filtration applications - Zhang, Tong (2013)
A novel microfiltration nanofibrous membrane assembled with a hierarchical TiO2/K-OMS-2 nanowire structure was fabricated and used for concurrent filtration, adsorption and photocatalytic oxidation in water treatment process.